A randomized pilot trial of a positive affect skill intervention (lessons in linking affect and coping) for women with metastatic breast cancer. Issue 12 (27th December 2016) - Cheung, Elaine O.; Cohn, Michael A.; Dunn, Laura B.; Melisko, Michelle E.; Morgan, Stefana; Penedo, Frank J.; Salsman, John M.; Shumay, Dianne M.; Moskowitz, Judith T.
Abstract: Background: We conducted a randomized pilot trial to examine the feasibility, acceptability, and preliminary efficacy of a 5 week positive affect skills intervention (LILAC: lessons in linking affect and coping) for women with metastatic breast cancer. Additionally, we examined whether online delivery of the intervention would offer comparable benefits as in‐person delivery. Methods: Women with metastatic breast cancer ( N = 39) were randomized to an in‐person intervention, online intervention, or in‐person attention‐matched control. Psychological well‐being (depression [Center for Epidemiologic Studies Depression Scale], positive and negative affect [Differential Emotions Scale], cancer‐specific quality of life [Multidimensional Quality of Life Scale—Cancer Version]), and positive coping (mindfulness, positive‐affect skill use, and self‐compassion [Self‐Compassion Scale: Short‐Form]) were assessed at baseline, 1 week post‐intervention, and 1 month post‐intervention follow‐up. Results: The LILAC intervention showed good feasibility, acceptability, and retention. Although the study was not adequately powered to detect between‐group differences in change on preliminary efficacy outcomes, within‐group comparisons revealed that LILAC participants (in‐person and online combined) showed reductions in depression and negative affect by the 1 month follow‐up ( d = −0.81). Notably, LILAC participants fell below the clinical threshold for depression (Center for Epidemiologic Studies Depression Scale = 16) by the 1 month follow‐up ( t [17] = −2.22, P = .04, d = −0.52), whereas control participants did not differ from threshold ( t [9] = 0.45, P = .66, d = 0.14). Conclusions: The LILAC intervention, regardless of delivery method, shows feasibility, acceptability, and preliminary efficacy for promoting psychological well‐being in women with metastatic breast cancer. This research provides support for a larger randomized trial to test more definitively the potential benefits of LILAC. A strength of the LILAC intervention includes its innovative focus on positive affect. The efficacy of the online delivery suggests the potential for widespread Internet dissemination.